1975
DOI: 10.1093/infdis/132.6.667
|View full text |Cite
|
Sign up to set email alerts
|

Selective Clearance of a Benign Clone of Venezuelan Equine Encephalitis Virus from Hamster Plasma by Hepatic Reticuloendothelial Cells

Abstract: A benign small-plaque clone of Venezuelan equine encephalitis virus was efficiently removed from the blood of inoculated hamsters by adsorption to cells of the hepatic reticuloendothelial system. More than 99% of infectious small-plaque virus, intrinsically labeled with 32P, was cleared from the blood within 30 min of inoculation; 47.6% of the 32P-labeled small-plaque virus inoculum was concentrated in the liver. In contrast, only 0.8% of a virulent large-plaque clone of the virus was cleared from the blood. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

1982
1982
2000
2000

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 16 publications
0
29
0
Order By: Relevance
“…Heparin-binding proteins tend to have very short half-lives in the circulation, being rapidly sequestered by tissue HS, particularly in the liver, which has the most highly sulfated HS of any organ (2,35,53,55 reported in several studies that plaque variants of alphaviruses are cleared at variable rates from the circulation after an intravenous injection, with LP variants typically having longer half-lives (19,20,40). Because it is now apparent that one of the factors contributing to increased plaque size is a decreased ability to bind to sulfated polysaccharides, we reexamined the elimination of virus from the circulation.…”
Section: Derivation Of Lp Virusesmentioning
confidence: 99%
See 3 more Smart Citations
“…Heparin-binding proteins tend to have very short half-lives in the circulation, being rapidly sequestered by tissue HS, particularly in the liver, which has the most highly sulfated HS of any organ (2,35,53,55 reported in several studies that plaque variants of alphaviruses are cleared at variable rates from the circulation after an intravenous injection, with LP variants typically having longer half-lives (19,20,40). Because it is now apparent that one of the factors contributing to increased plaque size is a decreased ability to bind to sulfated polysaccharides, we reexamined the elimination of virus from the circulation.…”
Section: Derivation Of Lp Virusesmentioning
confidence: 99%
“…The clearance of infectious virus shown here represents actual physical removal of the virus from the circulation and is not due merely to inactivation of infectivity. Previous studies have shown that alphaviruses, regardless of plaque size, are not inactivated by serum or whole blood (22,40), and clearance of radiolabeled alphaviruses from the circulation has been shown to follow kinetics identical to the clearance of PFU (20,21). In order to determine the organ distribution of virus following clearance from the circulation, various radiolabeled viruses were injected intravenously, and selected organs were collected after perfusion of the mice 30 min later.…”
Section: Derivation Of Lp Virusesmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies of nonimmune clearance of alphaviruses by hepatic sinusoidal cells have shown that avirulent strains were cleared from the circulation more rapidly than virulent strains (Jahrling and Sherer, 1973;Jahrling and Gorelkin, 1975;Jahrling, 1976) and that plasma clearance rates in vivo correlated with both increased affinity for cultured cells and pH attachment optima for macrophages near physiological pH (Marker and Jahrling, 1979). Clearance by macrophages of neurotropic flaviviruses is also an important determinant of the course of infection (Zisman et al, 1971;Monath and Borden, 1971;Olson et al, 1975).…”
Section: Viremiamentioning
confidence: 99%